Public privates : feminist geographies of mediated spaces - England, Marcia R. (University of Nebraska Press, 2018)
"Public Privates focuses on public and private acts and spaces in media to explore the formation of geographies. Situated at the intersections of cultural geography, feminist geography, and media studies, Marcia R. England's study argues that media both reinforce and subvert traditional notions of public and private spaces through depiction of behaviors and actions within those spheres. Though popular media contribute to the erosion of indistinct edges between spaces, they also frequently reinforce the traditional dualism through particular codings that designate the normed and gendered socio-spatial actions appropriate in each sphere--producing geographical imaginations and behaviors. England applies her immensely readable construction to a diverse and wide-ranging array of media including Buffy the Vampire Slayer, The Fast and the Furious, J-Horror, sitcoms, Degrassi, and reality TV. By examining the gendered representations of public and private spaces in media and how images influence imagined and lived geographies, England shows how popular culture, specifically visual media, transmits ideologies that disintegrate the already blurred boundaries between public and private spaces."--